Estado da arte dos trabalhos de conclusão de curso produzidos no curso de logística 2012 a 2021. - Soares, Matheus Gonçalves (Universidade Federal do Tocantins, 2023)
This work presents a bibliometric study on the academic productions of the Higher Course of Technology in Logistics at the Federal University of Tocantins, Araguaína-Cimba campus, from 2012 to 2021. Through the state of the art, with a bibliometric method and qualitative research, we seek to point out, by the titles, what is the possible field of activity of logistics and what is the methodology that predominates in these publications. To point out the field of action, those described in the National Catalog of Technological Courses were used as a parameter. The results demonstrate that, by the titles of the Course Conclusion Papers (TCC's) 19% of the trainees have the profile of managing operations and logistical processes and the type of research that most prevails making the mapping by the described methodologies is the bibliographic research, stands out with 72.25%. The study also highlighted the field of action